The Role of Ni and Co in Suppressing O‐Loss in Li‐Rich Layered Cathodes. (6th August 2020) - Boivin, Edouard; Guerrini, Niccolo; House, Robert A.; Lozano, Juan G.; Jin, Liyu; Rees, Gregory J.; Somerville, James W.; Kuss, Christian; Roberts, Matthew R.; Bruce, Peter G.
Abstract: Lithium‐rich transition metal cathodes can deliver higher capacities than stoichiometric materials by exploiting redox reactions on oxygen. However, oxidation of O 2− on charging often results in loss of oxygen from the lattice. In the case of Li2 MnO3 all the capacity arises from oxygen loss, whereas doping with Ni and/or Co leads to the archetypal O‐redox cathodes Li[Li0.2 Ni0.2 Mn0.6 ]O2 and Li[Li0.2 Ni0.13 Co0.13 Mn0.54 ]O2, which exhibit much reduced oxygen loss. Understanding the factors that determine the degree of reversible O‐redox versus irreversible O‐loss is important if Li‐rich cathodes are to be exploited in next generation lithium‐ion batteries. Here it is shown that the almost complete eradication of O‐loss with Ni substitution is due to the presence of a less Li‐rich, more Ni‐rich (nearer stoichiometric) rocksalt shell at the surface of the particles compared with the bulk, which acts as a self‐protecting layer against O‐loss. In the case of Ni and Co co‐substitution, a thinner rocksalt shell forms, and the O‐loss is more abundant. In contrast, Co doping does not result in a surface shell yet it still suppresses O‐loss, although less so than Ni and Ni/Co doping, indicating that doping without shell formation is effective and that two mechanisms exist for O‐loss suppression. Abstract : O‐loss from Li2 MnO3 can be almost completely suppressed with Ni substitution due to the presence of a near stoichiometric Ni‐rich rocksalt shell, acting as a self‐protecting surface layer against O‐loss. In contrast, Co‐substitution does not result in a surface shell but still suppresses O‐loss, although less effectively than Ni and Ni/Co‐cosubstitution.